Are we achieving the benchmark of retrieving 12 lymph nodes in colorectal carcinoma specimens? Experience from a tertiary referral center in India and review of literature - Kedar K Deodhar; Atul Budukh; Mukta Ramadwar; Munita Meenu Bal; S V Shrikhande (Indian Journal of Pathology and Microbiology, 2012)
Introduction: The number of lymph nodes (LNs) retrieved from a specimen of colorectal carcinoma may vary. Factors that can possibly affect LN yield are age of the patient, obesity, location of the tumor, neoadjuvant therapy, surgical technique and pathologist′s handling of the specimen. Aim: The aim of our study is to look at lymph node retrieval from colorectal cancer (CRC) specimens in our hands and review the literature. Materials and Methods: From May 2010 to January 2011, a total of 170 colorectal carcinoma cases were operated in our institute. Type of the surgeries, lymph node yield was looked at. Results: There were 103 (60.6%) males and 67 (39.4%) females. The commonest age group was 50-59 years (30.6%). The surgeries included 107 surgeries for rectal carcinoma (63%) and 63 surgeries for colonic carcinoma (37%). Sixty six (38.8%) cases had received preoperative chemoradiotherapy, whereas 104 (61.2%) cases were without adjuvant therapy. The total lymph node positivity (metastatic disease) was 44.7% .The overall mean lymph node yield was 12.68 (range 0-63; median 11). The mean lymph node harvest in the age group < 39 was 15.76 whereas, the lymph node harvest in the group more than 39 years old was 11.90. ( statistically significant; P=0.03). The mean lymph node yield from specimens of rectal cancers (10.30) was lower than the mean lymph node yield from specimens for colonic cancers (16.71);( statistically significant, P<0.01). There was also statistically significant difference between the mean LN yield in chemoradionaiive cases (14.63) and in the cases where neoadjuvant therapy was received, (9.59); P<0.01. Conclusion: Pathologist while assessing a specimen of CRC should aim to retrieve a minimum of 12 LN. Surgical expertise and diligence of the pathologists remain two main alterable factors that can improve this yield. Neoadjuvant or preoperative radiotherapy can yield in less number of nodes.